Analisis Kemandirian Keuangan Daerah dan Potensi Pertumbuhan Ekonomi pada Pemerintah Daerah Kabupaten Pemalang Tahun Anggaran 2019-2023 - Kory Dina Putri Jadmiko; Arie Pratama; Rosyani Muthya (P3M Politeknik Negeri Bengkalis, 2025)
The purpose of this study is to research the economic growth potential and financial independence level of the Pemalang Regency Government during the Fiscal Years 2019–2023. The main issue in this research is the low contribution of Locally-Generated Revenue (LGR) to the total regional income, which indicates a heavy reliance on transfer funds from the central government. This research uses a descriptive qualitative approach and financial ratio analysis. The analysis of regional financial independence involves the financial independence ratio, fiscal decentralization degree, financial dependency ratio, and LGR effectiveness. The results show that the average financial independence ratio of 16.76% is categorized as very low (instructive), indicating central government dominance in regional funding. The fiscal decentralization ratio of 13.77% is categorized as low, while the regional financial dependency ratio of 82.49% is very high. Nevertheless, LGR effectiveness reached 108.17%, categorized as very effective, demonstrating the region’s ability to meet revenue targets despite the relatively small value. The economic growth potential is analyzed through share, growth, and elasticity indicators. The average LGR share of regional expenditure is 16.83%, the average LGR growth rate is 4.26%, and the LGR elasticity to GRDP is 5.94%, indicating a very high responsiveness to economic growth. The Financial Capability Index (FCI) is 0.47, categorized as moderate. Therefore, Pemalang Regency has not yet achieved fiscal independence and possesses untapped economic growth potential.